2005
DOI: 10.1161/circulationaha.104.516948
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and 10-Year Cardiovascular Disease Risk in the Hoorn Study

Abstract: The metabolic syndrome, however defined, is associated with an approximate 2-fold increased risk of incident cardiovascular morbidity and mortality in a European population. In clinical practice, a more informative assessment can be obtained by taking into account the number of individual risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
367
4
20

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(412 citation statements)
references
References 30 publications
21
367
4
20
Order By: Relevance
“…However, the association we found between MetS and CHD risk, with ORs around 1.5, was not as strong as the associations reported in previous prospective studies from the United-States [3,4,6,7] and Northern-Europe [9,11,12] in middle-aged men, displaying a 2 or 3-fold higher risk for subjects with MetS. Nevertheless, hazard risk estimates of 1.5 to 2 after adjustments, close to those we observed, were found in the USA in the Atherosclerosis Risk in Communities study (ARIC) [3].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the association we found between MetS and CHD risk, with ORs around 1.5, was not as strong as the associations reported in previous prospective studies from the United-States [3,4,6,7] and Northern-Europe [9,11,12] in middle-aged men, displaying a 2 or 3-fold higher risk for subjects with MetS. Nevertheless, hazard risk estimates of 1.5 to 2 after adjustments, close to those we observed, were found in the USA in the Atherosclerosis Risk in Communities study (ARIC) [3].…”
Section: Discussioncontrasting
confidence: 99%
“…Metabolic syndrome (MetS) has been found associated with atherosclerosis [1,2] and risk of coronary heart disease (CHD) in the United-States [3][4][5][6][7] or in Northern-Europe [8][9][10][11][12], where cardiovascular incidence rates are elevated. There is in contrast much less information on the relationship between MetS and CHD risk in low risk populations from Southern-Europe, where the nutritional and environmental background is more favourable.…”
Section: Introductionmentioning
confidence: 99%
“…Differences across studies may also be related to the underlying study populations, particularly gender distribution. Only a limited number of studies have included both men and women, enabling a direct comparison between the sexes [13,[25][26][27][28]. In agreement with our results, most of these studies found higher RRs associated with MetS in women than in men [13,[25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, patients who were seen with 3 or more of the following 5 risk factors were defined as having MetS:

Central obesity, defined as waist circumference greater than established ethnicity‐specific values. Because the data on waist circumference were not available, for purposes of this analysis, we used the body mass index (BMI) >30 kg/m 2 as a criterion for classifying patients as obese 28, 29, 30. Other large studies have previously used this substitution and showed that there is a strong linear correlation between waist circumference and BMI value 30, 31, 32

…”
Section: Methodsmentioning
confidence: 99%